2017
DOI: 10.1186/s12891-017-1763-2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation under anesthesia versus physiotherapy treatment in stage two of a frozen shoulder: a study protocol for a randomized controlled trial

Abstract: BackgroundThere is no consensus about the optimal treatment strategy for frozen shoulders (FS). Conservative treatment consisting of intra-articular corticosteroid infiltrations and physiotherapy are considered appropriate for most patients. However, with a conservative strategy, patients experience a prolonged rehabilitation period with a considerable amount of pain and disabilities in daily life. Also, at long term, a residual amount of pain and restriction of range of motion is frequently reported. Manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…Recent developments in ultrasound technology have enabled its use with brachial plexus anesthesia or cervical root block [13][14][15][16]29]. Previous reports described good results like those of the present study in primary FS patients with or without diabetes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Recent developments in ultrasound technology have enabled its use with brachial plexus anesthesia or cervical root block [13][14][15][16]29]. Previous reports described good results like those of the present study in primary FS patients with or without diabetes.…”
Section: Discussionsupporting
confidence: 69%
“…Woods and Loganathan [30] found that patients with successful outcomes have significant improvement in pain within three to four days after MUA, and improvement in ROM within about three weeks. Kraal et al [29] also found that an initial period of one to 2 weeks of intensive physiotherapy after MUA is essential to prevent recurrence of restrictions and advocated more aggressive rehabilitation with intensive stretching and ROM exercises in the first weeks after MUA to preserve the obtained ROM. The importance of early rehabilitation is the same in ACR and MUA in terms of surgical treatment for joint stiffness [20].…”
Section: Discussionmentioning
confidence: 99%
“…Frozen shoulder is a condition characterized by spontaneous onset of pain, ROM restriction, stiffness and limitation of glenohumeral joint (1)(2)(3)(4)(5). Also defined adhesive capsulitis, it is an unknown etiology disorder (primary or idiopathic frozen shoulder); when it is associated with traumas or systemic diseases, such as diabetes mellitus II type, thyroid diseases, rheumatoid arthritis etc., it is defined secondary frozen shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory tells that if the immobilization due to injury and pain is kept up longer than necessary, it may lead to learned non-use, loss of cortical representation and then stiffness and pain (11). Early diagnosis is not easy: the first symptom is the onset of a nocturnal and daily pain causing restriction in function and daily activities (1)(2)(3)5); there is a loss of both passive and active movements, particularly a loss of more than 30° in passive external rotation (2); there is weakness of supraspinatus muscle and long head biceps lack of flexibility which cause limitation in abduction (12)(13)(14). In this pathologic mechanism the capsule does not become adhered to the humerus, but the contracted capsule holds the humeral head tightly against the glenoid fossa, causing a progressive loss of the physiological movements (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation